1983
DOI: 10.1149/1.2120062
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor Electrodes: XLIX . Evidence for Fermi Level Pinning and Surface‐State Distributions from Impedance Measurements in Acetonitrile Solutions with Various Redox Couples

Abstract: Capacitance-voltage (C-V) measurements were made for the single crystal semiconductors n-TiO2, n-CdS, n-InP, p-Si, p-GaAs, n-and p-WSe2, and n-MoSe2 in acetonitrile containing a number of redox couples whose potentials (Vredox) spanned a potential regime much wider than the bandgaps. The flatband potential (VrB) evaluated from capacitance-potential (C-V) measurements (Mott-Schottky plots) exhibited three types of behavior with varying solution redox potentials: (i) VFB varied monotonically with Vredo • for p-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 34 publications
3
48
0
Order By: Relevance
“…For ideal semiconductor/liquid junctions, no photoreduction of the redox species above the conduction and below the valence band edge should exist. It has been shown before, however, that the photoreduction of species with redox potentials more negative than the conduction band edges of p-type semiconductors (Ge, Si, InP, GaAs) is feasible (109)(110)(111)(112). This phenomenon is explained by Fermi-level pinning and/or unpinning of the band edges, which causes the photovoltage observed for a p-type semiconductor/liquid junction to become independent of the redox potentials of the electroactive species.…”
Section: Photoelectrochemical Reduction Of Co 2 By Semiconductor/molementioning
confidence: 99%
See 1 more Smart Citation
“…For ideal semiconductor/liquid junctions, no photoreduction of the redox species above the conduction and below the valence band edge should exist. It has been shown before, however, that the photoreduction of species with redox potentials more negative than the conduction band edges of p-type semiconductors (Ge, Si, InP, GaAs) is feasible (109)(110)(111)(112). This phenomenon is explained by Fermi-level pinning and/or unpinning of the band edges, which causes the photovoltage observed for a p-type semiconductor/liquid junction to become independent of the redox potentials of the electroactive species.…”
Section: Photoelectrochemical Reduction Of Co 2 By Semiconductor/molementioning
confidence: 99%
“…It can be concluded that as long as the reduction potential of the molecular catalyst is above the valence band edge of the p-type semiconductor, the photoreduction of the molecular electrocatalyst is feasible. Fermi-level pinning also places a limitation on the maximum photovoltage/open circuit voltage for a particular semiconductor/liquid junction to one-half the band gap of the semiconductor (109)(110)(111)(112). The stability of the semiconductor photocathode can be further enhanced by surface modification, either by covalent attachment or coating the surface with polymer films of the molecular electrocatalyst.…”
Section: Photoelectrochemical Reduction Of Co 2 By Semiconductor/molementioning
confidence: 99%
“…The reduction potential increases from -0.96 V vs. SCE for anthraquinone to 1.26 V vs. SCE for thianthrene (see ref. [72]). The open cicrcuit photopotential corresponds to the difference between the two energy levels, viz., E′ F -E 0 redox .…”
Section: Fermi-level Equilibrationmentioning
confidence: 99%
“…This band-edge shift with redox potential is a typical behavior of Fermi level pinning (34,36). Such a phenomenon was demonstrated with a very similar interface, p-Si immerged in a solvated electron solution (K + + e%(NH3)n) in liquid ammonia (23) where the dissolved K concentration could be controlled.…”
Section: Cyclic Voltammograms Under White Light Illumination-mentioning
confidence: 70%